Vitrificación de tejido ovárico porcino: efecto de diferentes agentes crioprotectores en la preservación de la morfología de folículos preantrales - Gabriel, P. (2012)
Ovarian tissue vitrification allows storage of large numbers of oocytes contained in preantral follicles (PAF). The aim of the present study was to analyze the effect of different combinations of crioprotective agents in the preservation of porcine PAF histologic structure during the exposition (toxicity) and vitrification processes. The responses of oocytes to ethylene glycol, dimethyl sulfoxide (DMSO) and a combination of both, with the addition of sucrose (0,25 M), and to ethylene glycol associated to growing concentrations of sucrose (0M; 0,25M; 0,75M and 1,0M) were analyzed. Primordial PAF treated with ethylene glycol presented fewer morphological abnormalities than the ones exposed to DMSO and ethylene glycol + DMSO combined (Control: 87%; etilenglicol: 52%; DMSO: 17% y etilenglicol + DMSO: 26%; Friedman p<0,05). In primary PAF, etilenglicol was the least toxic (Control: 70%; etilenglicol: 34%), while vitrification response of the ethylene glycol + DMSO group was superior (20%). Vitrification with growing concentration of sucrose led to reduction of normal primordial follicles percentage (Control: 64%; 0M: 48%; 0,25M: 42%; 0,75M: 12%; 1M: 9%). In all treatments, primary follicles were more damaged. In conclusion, the culture media of choice for vitrification was TCM 199-Hepes with 30% etilenglicol and 0 or 0,25M sucrose.